2020
DOI: 10.1073/pnas.1918163117
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid ALX/FPR2 regulates vascularization following tissue injury

Abstract: Ischemic injury initiates a sterile inflammatory response that ultimately participates in the repair and recovery of tissue perfusion. Macrophages are required for perfusion recovery during ischemia, in part because they produce growth factors that aid in vascular remodeling. The input signals governing this pro-revascularization phenotype remain of interest. Here we found that hindlimb ischemia increases levels of resolvin D1 (RvD1), an inflammation-resolving lipid mediator that targets macrophages via its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 58 publications
(77 reference statements)
3
39
0
Order By: Relevance
“…25) in rat muscle 3 days after synergist ablation at levels ~2-fold higher than baseline. Nevertheless, Sansbury et al 2020 reported that RvD1 is indeed present within mouse skeletal muscle tissue, at very low concentrations (36).…”
Section: Discussionmentioning
confidence: 99%
“…25) in rat muscle 3 days after synergist ablation at levels ~2-fold higher than baseline. Nevertheless, Sansbury et al 2020 reported that RvD1 is indeed present within mouse skeletal muscle tissue, at very low concentrations (36).…”
Section: Discussionmentioning
confidence: 99%
“…Specialized pro‐resolving mediators are produced in response to muscle injury (Giannakis et al, 2019; Markworth et al, 2020; Sansbury et al, 2020; Zhang et al, 2016) or physiological stress (Gangemi et al, 2003; Markworth et al, 2013; Vella et al, 2019; Zheng et al, 2019) implicating a role for these metabolites in muscle remodeling (Markworth et al, 2016). Current approaches to clinical management of soft tissue injuries focus predominantly on blocking cyclooxygenase (COX) mediated production of pro‐inflammatory prostaglandins with non‐steroidal anti‐inflammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of resolution agonists, termed immunoresolvents, can limit inflammation and expedite its resolution, while simultaneously relieving pain and stimulating tissue repair 46 . Unlike NSAIDs that may interfere with musculoskeletal tissue remodeling, 26 remarkably immunoresolvents were recently found to rather exert overall pro‐regenerative actions following skeletal muscle injury 47‐52 …”
Section: Introductionmentioning
confidence: 99%